The Relationships Between the Postmodern Agenda and the Bases of Teacher Education Policies in Brazil - Masson, Gisele (Education Policy Analysis Archives, 2011)
This paper attempts to show the relationships between the Postmodern agenda and the bases of initial teacher education policies in Brazil. After describing the assumptions of the postmodern agenda, it describes the bases of initial teacher education policies and shows the main problems of the influence of the postmodern agenda on initial teacher education. The topic of this essay is relevant to the field of education policies, since initial teacher education can contribute either to the reproduction of a pragmatist/utilitarian education or to the construction of an education project according to the working class interests. With regard to the methodology, this research was based on the historical and dialectical materialism and used bibliographical and documentary sources. This study made it possible to conclude that since the 1990’s teacher education policies in Brazil have adapted to pragmatic, relativistic and subjectivist ideas, especially by praising the epistemology of practice, considering the concept of reflective teacher and the logic of competences. The postmodern agenda has many points in common with teacher education policies regarding the emphasis on local, ephemeral and short-sighted actions, whereupon social reality is seen as fragmented, multifarious, fluid and plural rather than as an integral unity. Within the context of teacher education, this can be clearly observed in the fragmentation of actions, projects, resources and educational entities, in contrast to a consistent and integrated proposal, which is what a policy of State and nation should be.